Effect of heat treatment on pre-stocking of Turkey eggs and its impact on incubation and hatching - Filho J.K.* (2020)
© 2019 Elsevier LtdEgg stocking is used to meet housing demands in the hatchery industry. Stocking periods longer than 10 days of occur commonly, despite the fact that this practice causes productive losses during the incubation process. To minimize these losses, eggs are heated before incubation to stimulate the embryo, thereby reducing the range of birth intervals. The objective of this study was to determine whether heat treatment (37.5 °C) prior to incubation would improve hatching rates. We also determined the heat-exposure time necessary to improve productivity. We stored 5376 Nicholas pedigree eggs, aged between 40 and 51 weeks, for seven days. These eggs were distributed in three groups: groups 1 and 2 received 4 and 6 h of heat treatment, respectively; group 3 was used as control (no heat treatment, remaining at 17 °C). After heat treatment, the eggs were stored for 7 days at 17 °C, together with eggs from the control group. We found significant variation in the cumulative dispersion of birds born during the hatch window; greater numbers of birds were born in group 1 that underwent the 4-h heat treatment with a 24-h hatch window and in group 3 that underwent the 6-h heat treatment with a 12-h hatch window. Hatch rate, yolk retention and the relationship between average chick weight/average egg weight did not differ between treatments. These data suggest that heat treatment modulates the hatch window; nevertheless, the treatment did not influence the average weight the chicks, the number of chicks born, the percentage of hatching or yolk retention.